Fundamentals of ethnics for scientists and engineers - Seebauer, Edmund G. (Oxford University Press, 2001)
The book is composed of four units. The first two focus on ethical reasoning, outlining within the context of science and engineering the notions of character formation and intention central to virtue theory. To prepare students to handle complex ethical questions, these units extend virtue theory in a readily understandable way, accounting systematically for the consequences that follow an ethical decision. The second two units focus on practical issues such as intellectual property, conflict of interest, whistle blowing, and authorship in scientific publication. These units also treat more advanced topics like risk, resource allocation, conflicting ethical methods, and intuition in ethical decision making.